Environmental determinants of chironomid communities in remote northern lakes across the treeline – Implications for climate change assessments. (February 2016) - Luoto, Tomi P.; Rantala, Marttiina V.; Galkin, Annukka; Rautio, Milla; Nevalainen, Liisa
Highlights: We examined treeline lakes in subarctic Lapland for their chironomid assemblages. The aim was to assess the influence environmental factors on the communities. Organic content, TN, water depth and pH had significant influence on chironomids. Sites with high DOC and benthic microbial mats had distinctive communities. Our results create basis for climate change assessments in remote northern areas. Abstract: Chironomids ( Diptera : Chironomidae ) in northern lakes are especially sensitive to climate change impacts. In addition, environmental factors other than direct temperature increase might play an important role in functioning of these keystone aquatic communities. We examined 31 lakes at the treeline ecotone in subarctic Finnish Lapland for their surface sediment chironomid fauna to assess the influence of different environmental factors on the communities. We aim to improve understanding of the climate-driven catchment and limnological factors, for the assessment of climate change impacts. Our results indicated that organic content of the sediment, total nitrogen, water depth and pH that are all likely to change under global warming had statistically significant influence on the chironomid assemblages and associated indicator taxa were assigned for these variables. In addition, a dissolved organic carbon (DOC) threshold (4 mg l −1 ) was observed that divided the study sites based on their chironomid composition. Sites with high DOC concentrations and benthic microbial mats had distinctive chironomid fauna from low-DOC sites without microbial mats indicating the significance of benthic versus planktonic productivity in the structure and functioning of polar lakes. The results provide important knowledge on chironomid-environmental relationships in climate-sensitive subarctic lakes and create basis for chironomid-based environmental change assessments in remote northern areas.